(untitled) (Marketing Journal, 2025)
The article analyzes the functioning mechanisms of human resource training management, particularly the types of ensuring its economic interrelation with innovative entrepreneurial activity. Specifically, based on a comparative analysis of different types of human resource training management, opportunities for the development of innovative entrepreneurial activity have been identified.